1812 : the war that forged a nation - Borneman, Walter R., 1952- (New York : HarperCollins Publishers, 2004)
"Here are the stories of commanding generals such as America's Henry "Granny" Dearborn, double-dealing James Wilkinson, and feisty Andrew Jackson, as well as Great Britain's gallant Sir Isaac Brock, overly cautious Sir George Prevost, and Rear Admiral George Cockburn, the man who put the torch to Washington. Here too are those inadvertently caught up in the war, from heroine farm wife Laura Secord, whom some call Canada's Paul Revere, to country doctor William Beanes, whose capture set the stage for Francis Scott Key to write "The Star-Spangled Banner."" "1812: The War That Forged a Nation presents a sweeping narrative that emphasizes the struggle's importance to America's coming-of-age as a nation. Though frequently overlooked between the American Revolution and the Civil War, the War of 1812 did indeed span half a continent - from Mackinac Island to New Orleans and Lake Champlain to Horseshoe Bend - and it paved the way for the conquest of the other half."--BOOK JACKET.
Drumbeats (1807-1812). To steal an empire -- First blood at sea -- War hawks and Tippecanoe -- Mr. Madison's war -- Concessions too late -- Bugles (1812-1814). Oh, Canada -- Hurrah for Old Ironsides -- Marching on a capital -- Don't give up the ship -- We have met the enemy -- Old Hickory heads south -- On the Thames and the St. Lawrence -- The lion's roar -- Finale (1814-1815). Niagara's thunder -- Lake Champlain -- Another capital burns -- O say, can you see? -- Still Mr. Madison's war -- Christmas in Ghent -- Along the mighty Mississip' -- A nation at last.
Includes bibliographical references (p. [327]-333) and index.
Keywords: United States -- History -- War of 1812.; United States -- History -- War of 1812 -- Influence; Britisch-Amerikanischer Krieg